Introduction to counseling and guidance - Gibson, Robert L. (Prentice Hall India, 2008)
The latest edition of this highly acclaimed international text retains its logical progression of topics while introducing the latest technologies concepts and applications as selected by the counselors. It presents practical examples and discussions of all the major facets of counseling in a wide range of counselors work settings. The text explains the techniques of assessment including an overview of standardized testing and discussion of subjective approaches to appraisal such as observation self-reporting and others. The book is designed for use in courses related to education psychology education and counseling and guidance. Also the book will provide a comprehensive overview of the subject to professionals from the field of counseling. The stress of the book is on giving a broad general discussion to the reader.